Evaluation of Nursing Students’ Attitudes Toward Health Technologies in Clinical Practice and Individual Innovative Behaviors: A Cross-sectional and Correlational Study - İlgün ÖZEN ÇINAR; Fadime Hatice İNCİ; Nazan KOŞTU; Edanur ÖZKAYA BOZKURT (Bezmiâlem Science, 2025)
Objective: Future nurses’ effective use of health technologies requires sufficient knowledge, positive attitudes, individual innovativeness, and self-efficacy behaviors toward these technologies. This study examined nursing students’ health technology attitudes and individual innovativeness behaviors. Methods: This cross-sectional and correlational study involved 346 students with practice experience in the nursing department of a university. Identification form, the Health Personnel Health Technology Assessment Attitude Scale, and the Individual Innovativeness Scale (IIS) were used. Descriptive statistics and correlation test were used. Results: The mean total score of the Healthcare Personnel Health Technologies Assessment Attitude Scale was 99.58±10.65, and the mean total score of the IIS was 63.65±9.40. A weak positive correlation was found between students’ health technology evaluation attitudes and individual innovativeness behaviors. Conclusion: Health technology should be included in the education of future nurses to teach technological tools, eliminate barriers to their use, and develop innovative behaviors. Positive attitudes will bring along innovative behaviors and ensure faster adoption of developments in health technologies. At this point, it is imperative to support the existing positive attitudes of students and encourage their innovative behaviors.